長期回遊中キタゾウアザラシのファインスケールでの採餌行動 - 安達, 大輝; 高橋, 晃周; Melinda, Fowler; Nicole, Teutschel; Luis, Huckstadt; Daniel, Costa; 依田, 憲; 内藤, 靖彦; Taiki, Adachi; Akinori, Takahashi; Ken, Yoda; Yasuhiko, Naito (2010)
第32回極域生物シンポジウム ポスター発表 conference object